2019
DOI: 10.1038/s41598-019-46358-7
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 regulates DNA damage-induced nucleolar-nucleoplasmic shuttling of WRN and XRCC1 in a toxicant and protein-specific manner

Abstract: The prime function of nucleoli is ribogenesis, however, several other, non-canonical functions have recently been identified, including a role in genotoxic stress response. Upon DNA damage, numerous proteins shuttle dynamically between the nucleolus and the nucleoplasm, yet the underlying molecular mechanisms are incompletely understood. Here, we demonstrate that PARP1 and PARylation contribute to genotoxic stress-induced nucleolar-nucleoplasmic shuttling of key genome maintenance factors in HeLa cells. Our wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…In addition, phosphorylation was proposed to modulate WRN's subnuclear localization [39,68]. Consistent with the idea that such DNA damage-induced protein dynamics are regulated in a stress-specific manner, we recently found that after treatment with H 2 O 2 and the alkylating agent 2-chloroethyl ethyl sulfide (CEES), but not the topoisomerase inhibitor camptothecin (CPT), nucleolar-nucleoplasmic translocation of WRN was dependent on the PARP1 protein, yet independent of its enzymatic activity [69].…”
Section: How Do Nucleoli Respond To Stress and Dna Damage?supporting
confidence: 58%
See 2 more Smart Citations
“…In addition, phosphorylation was proposed to modulate WRN's subnuclear localization [39,68]. Consistent with the idea that such DNA damage-induced protein dynamics are regulated in a stress-specific manner, we recently found that after treatment with H 2 O 2 and the alkylating agent 2-chloroethyl ethyl sulfide (CEES), but not the topoisomerase inhibitor camptothecin (CPT), nucleolar-nucleoplasmic translocation of WRN was dependent on the PARP1 protein, yet independent of its enzymatic activity [69].…”
Section: How Do Nucleoli Respond To Stress and Dna Damage?supporting
confidence: 58%
“…We hypothesized that in case of WRN, PARP1 and an additional unknown factor mediate the release of WRN from nucleoli, while XRCC1 requires nucleoplasmic DNA damage-bound and PARylated PARP1 as a loading platform, which leads to XRCC1 retention in the nucleoplasm until its tasks in BER are completed. This notion is supported by findings revealing that in cells without PARP1 activity, XRCC1 relocates quickly to nucleoli upon DNA damage induction [69].…”
Section: Nucleolar Functions Of Parp1mentioning
confidence: 69%
See 1 more Smart Citation
“…In a previous study, we revealed that XRCC1 translocates from nucleoli to the nucleoplasm upon H 2 O 2 treatment. In the presence of PARP1, XRCC1 is retained in the nucleoplasm, while in PARP1 KO cells, XRCC1 swiftly relocates back into nucleoli ( 65 ). In accordance with this, Figure 8 shows that in PARP1\WT-reconstituted cells, XRCC1 was released from nucleoli in response to H 2 O 2 -treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic images were acquired using either a Zeiss Axiovert 200M widefield microscope (for PAR detection) or a Zeiss LSM700 confocal microscope (for XRCC1 and fibrillarin detection). Image data was analyzed using automated KNIME workflows as described previously ( 34 , 65 ). Only cells with a GFP fluorescence signal >1.5-fold of the mean background fluorescence were considered as GFP-positive and thus analyzed for PAR, XRCC1 and fibrillarin.…”
Section: Methodsmentioning
confidence: 99%